The Feasibility of Farmer-Led Cooperatives for Southwest Florida Farm to School Procurement - Jonathan Adam Watson; Danielle D. Treadwell; Catherine Campbell; Ray Bucklin (EDIS)
Florida’s K–12 schools provide a potential opportunity to increase market channel options for small- and mid-sized diversified farms, but processing, storage, and distribution resources are extremely limited for smaller producers. This 9-page document serves as a model and case study with steps for producers and other stakeholders to conduct a feasibility study before forming a cooperative to sell local fruits and vegetables to schools and other institutional food-service outlets. Written by Jonathan Adam Watson, Danielle D. Treadwell, Catherine Campbell, and Ray Bucklin, and published by the UF/IFAS Department of Agricultural and Biological Engineering, March 2021.